Spin freezing and field induced transition in (Tb1−xEux)2Ti2O7: A magnetic property study - Singh, P.; Pal, A.; Gangwar, V.K.; Ghosh, S.; Singh, R.K.; Ghosh, A.K.; Chatterjee, S. (Elsevier B.V., 2020)
The magnetic properties and Raman effect of (Tb1−xEux)2Ti2O7 have been investigated. Raman study indicates the existence of hardening due to phonon-phonon anharmonic interaction. The DC magnetic study indicates the significant contribution of dipolar and exchange interactions in Eu rich samples. From AC magnetic measurement, a partial single ion spin freezing around Tf = 33 K at zero magnetic field is observed in (Tb1−xEux)2Ti2O7. On applying a field of 10 kOe, all compounds show a field induced transition which shifts towards higher temperature with increase Eu content. This field induced transition might be attributed to the single moment saturation. © 2019 Elsevier B.V.
Keywords: Spin freezing; transition; magnetic property